THE IMPACT OF INTERGOVERNMENTAL TRANSFERS ON THE FINANCIAL SECURITY OF THE CONSTITUENT ENTITIES OF THE RUSSIAN FEDERATION - M. Kotov, Roman; M. Chernysheva, Nuriya (Revista Gênero e Interdisciplinaridade, 2020)
The research focuses on the mechanism of inter-budget transfers in the budget system of the Kemerovo Oblast. The evolution of inter-budgetary relations of the RF is discussed, models of separating the powers are given, implementation of the regional budget and that of municipalities are analyzed, and the role of inter-budget transfers in leveling budgetary provision is revealed. The research aims to identify promising areas for strengthening regional and local budgets in the Kemerovo Oblast. The crucial method is to analyze the structure and dynamics of the budgets of the Kemerovo Oblast and its municipalities, as well as to look into inter-budget transfers. The dynamics and structure of intergovernmental transfers are investigated using economic and statistical analysis. Based on the results, an assessment is made of the existing model for implementing the mechanism of inter-budget transfers, the directions for reforming this mechanism are stated, and sources of increasing the revenue side of budgets are identified to reduce the dependence of the regional budget on the federal one.